2017
DOI: 10.7324/japs.2017.70806
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Stevia rebaudiana and Aspartame on hepato-renal function of diabetic rats: Biochemical and Histological Approaches

Abstract: Diabetes mellitus is a chronic syndrome affecting many systems of the body and may be considered as a leading cause of death globally. To compare the efficacy of Stevia rebaudiana and Aspartame on hepato-renal functions, sixty adult male albino rats were divided into 6 groups; control, Stevia, Aspartame, diabetic, diabetic-treated with Stevia and diabetic-treated with Aspartame. Food consumption, body weight, blood glucose, serum aspartate transaminase (AST), alanine transaminase (ALT), alkaline phosphatase (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Aspartame, a non-caloric sweetener, has been suggested to decrease body weight and food intake in rats and affect carbohydrate and lipid metabolism. Furthermore, it increases energy expenditure [21]. These results agree with ours as aspartame treatment showed a significant decrease in body weight after 60-day treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Aspartame, a non-caloric sweetener, has been suggested to decrease body weight and food intake in rats and affect carbohydrate and lipid metabolism. Furthermore, it increases energy expenditure [21]. These results agree with ours as aspartame treatment showed a significant decrease in body weight after 60-day treatment.…”
Section: Discussionsupporting
confidence: 92%
“…The result of the present study is in agreement with the study of Anton et al (2010) and Abd-Elwahab et al (2017) [34,35] who used data to find that sweeteners ASP can affect both fat and carbohydrate metabolism in addition to increasing energy expenditure. Consequently, the results showed a significant decrease in body weight in the diabetes control group compared to the body weight of the normal control group .…”
Section: The Change In Body Weightsupporting
confidence: 93%
“…Recent studies declared that, the decreased body weight in aspartame treated mother's rats may be due to direct inhibitory effect of aspartame on the appetite center (Anton et al, 2010;AbdElwahab et al, 2017;Otman & Bin-Jumah, 2019). The obtained data suggests that low calorie sweeteners of aspartame can accelerate both lipids and carbohydrates metabolism leading to decrease in body weight.…”
Section: Discussionmentioning
confidence: 84%
“…Several studies revealed that food additives including MSG and aspartame have been implicated in induction of harmful effects on the different body organs (Moore, 2003;Waer and Edress, 2006;El-Beltagy, 2016;AbdElwahab et al, 2017). Also, Banderali et al (2000) added that utilization of food additives during pregnancy and breastfeeding has dangerous effects on both mothers and their offspring.…”
Section: Discussionmentioning
confidence: 99%